Research advance in the diversity and ecology of Oncaeidae. - Sun, R.X., Y.G. Wang, M. Lin, B.P. Xing, X.Y. Chen, P. Xiang & C.G. Wang (Biodiversity Science, 2021)
Oncaeidae are small copepods that serve an important role in marine ecosystems, with high abundance and rich diversity. Studies on the taxonomic diversity of these species still have great deficiencies, and its ecological function status may be underestimated. To improve the understanding of Oncaeidae, this paper reviews the research progress of taxonomy, species diversity, distribution and ecology of Oncaeidae, and also discusses the difficulties and technological trends in research of global Oncaeidae diversity.